La Convention d’indemnisation directe : 1978-1988 - Lapointe, Claude (Assurances, 1989)
With the arrival in Quebec of the Automobile Insurance Act, numerous questions were being asked concerning the Direct Compensation Agreement implemented in 1978. Ten years later, Mr. Claude Lapointe of the Groupement des assureurs automobiles du Québec, has, at our invitation, written an article to mark the anniversary of this agreement. His article looks at the Direct Compensation Agreement as it now stands compared with its initial objectives. Mr. Lapointe's text touches upon some very interesting aspects, such as subrogation and arbitrage, and also certain problems of application, though these are rather rare. The author concludes by stating that the Direct Compensation Agreement has met the needs of the users, that is, quick settlements at low costs and less disputes.